2012
DOI: 10.1007/s00427-012-0429-1
|View full text |Cite
|
Sign up to set email alerts
|

Stem cell dynamics in Cnidaria: are there unifying principles?

Abstract: The study of stem cells in cnidarians has a history spanning hundreds of years, but it has primarily focused on the hydrozoan genus Hydra. While Hydra has a number of self-renewing cell types that act much like stem cells--in particular the interstitial cell line--finding cellular homologues outside of the Hydrozoa has been complicated by the morphological simplicity of stem cells and inconclusive gene expression data. In non-hydrozoan cnidarians, an enigmatic cell type known as the amoebocyte might play a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
107
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(113 citation statements)
references
References 149 publications
5
107
1
Order By: Relevance
“…Such responses are tightly bound to some sort of "immune response, " i.e., the infiltration in the wound area of immune cells. This varies between organisms, and ranges from the transient intervention of amoeboid cells in cnidarians to the complex adaptive immune response of vertebrates (Kawakami and Nakanishi, 2001;Eming et al, 2009;Nakanishi et al, 2011;Palmer et al, 2011;Gold and Jacobs, 2013;Dubuc et al, 2014;Wenger et al, 2014). The relationship between wound healing, particularly the immune response phase, and the regenerative event is not clear, and is probably not a conserved feature (see next section).…”
Section: Wound Healingmentioning
confidence: 99%
See 2 more Smart Citations
“…Such responses are tightly bound to some sort of "immune response, " i.e., the infiltration in the wound area of immune cells. This varies between organisms, and ranges from the transient intervention of amoeboid cells in cnidarians to the complex adaptive immune response of vertebrates (Kawakami and Nakanishi, 2001;Eming et al, 2009;Nakanishi et al, 2011;Palmer et al, 2011;Gold and Jacobs, 2013;Dubuc et al, 2014;Wenger et al, 2014). The relationship between wound healing, particularly the immune response phase, and the regenerative event is not clear, and is probably not a conserved feature (see next section).…”
Section: Wound Healingmentioning
confidence: 99%
“…However, multipotent somatic cells, called interstitial cells (i-cells), have only been described in hydrozoans (Leclère et al, 2012;Gold and Jacobs, 2013) where they can coexist with other restricted stem cells capable of differentiation into more specialized cell types (Müller et al, 2004;Hobmayer et al, 2012;Gold and Jacobs, 2013). Homologues of i-cells seem to be absent in other classes of cnidarians.…”
Section: Precursors: Origin Of Regenerating Elementsmentioning
confidence: 99%
See 1 more Smart Citation
“…3G). The cells of the main body column divide continuously and these replace all of the non-dividing, differentiated cells in the hydra within 20 days; thus the hydra’s body is renewed continuously - at least 60 times over the 4 years of the Martínez study (Martínez, 1998; Watanabe et al, 2009; Tanaka and Reddien, 2011; Gold and Jacobs, 2013). Hydras typically maintain a steady adult size; most excess cells are formed into buds that develop into daughter hydras that separate from their mother (Fig.…”
Section: Aging In Basal Metazoans – Among Three Lesser Groups Of Bmentioning
confidence: 99%
“…Studies revealed that, in contrast to the prevalence of diverse oligopotent and unipotent stem cells of vertebrates, marine invertebrates appear to display the communal spread of multipotency and pluripotency [10], with adult stem cells that give rise to cell lineages characteristic of more than a single germ layer, sometimes with somatic and germ line potential. In addition, unlike vertebrates, in many aquatic/marine invertebrates, stem cells are disseminated and widespread inside the animal body, i.e., not associated with a regulatory microenvironment (niche) [12,13]. It is also worthy of note that transdifferentiation (today, a topic of great interest when trying to understand how to "reprogramme" a cell) is prevalent in both anatomically simple and "morphologically complex" invertebrates [14,15].…”
Section: Relevance and Timelinessmentioning
confidence: 99%